Feeding Astragalus membranaceus Root Improves the Rumen Fermentation Rate in Housed Goats through the Alteration of the Rumen Community Composition - Peng, Zhaoyu; Fujino, Mizuki; Anand, Mukul; Uyeno, Yutaka (Microorganisms (Basel), 2024)
Although Astragalus membranaceus root (AMR) has been noted as an ingredient in ruminant feed, the impacts of AMR feeding on rumen fermentation and the microbial community structure within the rumen are yet to be evaluated. This study investigated the effects of AMR supplementation on rumen fermentation characteristics and microbial community structures in goats. In two sets of feeding experiments, four Japanese native goats were fed AMR (10 g/kg DM/day/head) for three weeks per experiment. The rumen fluid samples were analyzed using high-performance liquid chromatography for fermentation products and next-generation sequencing for microbial analysis. The rumen fluid samples in the second experiment were also subject to an in vitro anaerobic fermentation test. The results indicated a significant modification, with a higher volatile fatty acid (VFA) content in the rumen fluid of goats in the feeding period than before feeding (p < 0.01). The microbial analysis revealed a significant increase in community diversity (p < 0.05) following AMR feeding, and the rumen bacterial community increased in two families belonging to the order Oscillospirales in Firmicutes (p < 0.05). The phylum Verrucomicrobiota was observed to be significantly less abundant after AMR feeding than during the control period (p < 0.05). Notably, the linear discriminant analysis revealed that the families with largely unknown functions in the rumen (Oscillospiraceae, Rikenellaceae, Muribaculaceae, and vadinBB97) were the determinants of the community split between control and AMR feeding. Increased fermentation rate by AMR feeding was also supported by an in vitro culture experiment, which resulted in faster VFA production without affecting methane production in total gas production. The study demonstrated that AMR can significantly facilitate change in the bacterial community structure in the goat rumen involving a shift of the favoring fibrolytic bacteria towards VFA production. The long-term effects of AMR supplementation and its applicability across different ruminant species, with potential benefits for animal health and productivity, should be addressed.